2002
DOI: 10.1097/00001888-200205000-00011
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Tool to Evoke Physiciansʼ Real Training Needs

Abstract: Commonly used methods for identifying the training needs of general practitioners do not enable the real needs felt during interviews with patients during office visits to be detected. In this study, the authors evaluate how physicians' use of a personal-office-visit diary affects the level of specificity of their expressed training needs. In 1999, the authors carried out a controlled intervention trial using a random sample of 1,038 general practitioners from a region of France, randomized to intervention and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Evidence strongly suggests that clinicians have a limited ability to accurately self‐assess competence or performance, 39 as opposed to multifaceted clinical skill appraisals that include direct observation of clinical consultations by external assessors 40 . Performance can be enhanced by targeted learning packages based on the needs assessment of individual clinicians, 41 including use of individual practice audits and patient diaries 42,43 …”
Section: Resultsmentioning
confidence: 99%
“…Evidence strongly suggests that clinicians have a limited ability to accurately self‐assess competence or performance, 39 as opposed to multifaceted clinical skill appraisals that include direct observation of clinical consultations by external assessors 40 . Performance can be enhanced by targeted learning packages based on the needs assessment of individual clinicians, 41 including use of individual practice audits and patient diaries 42,43 …”
Section: Resultsmentioning
confidence: 99%
“… Gap or discrepancy analysis: comparing performance and competencies by self‐assessment or peer assessment, or objective testing. Individuals reflecting on their performance during or after a defined event. Self‐assessment by diaries, journals, log books, etc. Doctors who keep a diary of learning issues might be able to generate more specific learning objectives than those who do not 9 Peer review: whereby doctors assess and provide feedback to each other. Observation of doctors performing tasks that can be rated by an observer. Critical incident review and/or significant event auditing. Practice review, for example, review of notes, records, prescribing, letters, referrals, investigation requests, etc. …”
Section: Introductionmentioning
confidence: 99%
“…Self‐assessment by diaries, journals, log books, etc. Doctors who keep a diary of learning issues might be able to generate more specific learning objectives than those who do not 9 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perol et al showed that doctors who kept an office visit diary of learning issues were able to generate more specific learning objectives than those who did not 12. The importance of this observation relates to the observation by Bergus et al that the structure of clinical questions is key to obtaining useful answers from consultants 13.…”
Section: What Is the Way Forward?mentioning
confidence: 99%